Pore Structure and Fractal Characteristics of Organic-Rich Lacustrine Shales of the Kongdian Formation, Cangdong Sag, Bohai Bay Basin - Pan, Shouxu; Zha, Ming; Gao, Changhai; Qu, Jiangxiu; Ding, Xiujian (Frontiers in Earth Science, 2021)
In order to examine the pore structure and reveal the fractal geometric nature of shales, a series of laboratory experiments were conducted on lacustrine shale samples cored from Kongdian Formation. Based on the low temperature nitrogen adsorption, fluorescent thin section and field emission scanning electronic microscope, a comprehensive pore structure classification and evaluation was conducted for shale samples collected from the 2nd member of the Kongdian formation in the Cangdong sag. Fractal dimensions D1 and D2 (with relative pressure of 0-0.45 and 0.45-1.00, respectively) were obtained from the nitrogen adsorption data using the fractal Frenkel-Halsey-Hill (FHH) method. By additional means of X-ray diffraction analysis, TOC content analysis and thermal maturity analysis, the relationships between pore structure parameters, fractal dimensions, TOC content and mineral composition are presented and discussed in this paper. The results show that interparticle pores and microfractures are predominant, whereas organic matter pores are rarely found. The pore morphology is primarily featured with wide-open ends and slit-shaped structures. In terms of pore scale, mesopores and macropores are predominant. The value of fractal dimension D1 representing small pores ranges from 2.0173 to 2.4642 with an average of 2.1735. The value of D2 which represents large pores ranges from 2.3616 to 2.5981 with an average of 2.4960. These low numbers are an indication of few pore types and relatively low heterogeneity. In addition, smaller D1 values reveal that large pores have more complicated spatial structures than smaller ones. The results of correlation analysis show that: 1) D2 is correlated positively with specific surface area but negatively with average pore diameter; 2) D1 and D2 literally show no obvious relationship with mineral composition, TOC content or Ro; 3) both total BJH volume and specific surface area show a positive relationship with dolomite content and a negative relationship with felsic minerals content. These results demonstrate that the pore types are relatively few and dominated by mesopores, and the content of brittle minerals such as dolomite and felsic minerals control the pore structure development whilst organic matter and clay minerals have less influence due to low thermal maturity and abundance of clay minerals.